1977
DOI: 10.2307/1589424
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Viscerotropic Velogenic Newcastle Disease Virus and Pet Birds of Six Species. I. Clinical and Serologic Responses, and Viral Excretion

Abstract: Clinical and serologic responses to a psittacine isolate of viscerotropic velogenic Newcastle disease virus (VVNDV) were evaluated in pet birds of six species: budgerigar, yellow-headed Amazon parrot, halfmoon conure, lesser hill mynah, black-headed nun, canary. The clinical response was most marked in the budgerigars, parrots, and conures, and only minimal in the nuns. Between post-exposure days (PED) 3 and 5 some birds developed ruffled plumage, conjunctivitis, and central nervous system dysfunction: ataxia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 3 publications
1
21
0
2
Order By: Relevance
“…Since the trading of these birds across regional and international boundaries is extensive (over 400,000 nonpoultry birds have been imported into Japan each year for the last 5 years), the risk of worldwide dissemination of potentially virulent NDVs is considerable. Researchers have speculated that the various types of NDV have been introduced via the importation of various kinds of birds, since NDV can persist in birds in an inapparent carrier state (5,9,10,40).…”
mentioning
confidence: 99%
“…Since the trading of these birds across regional and international boundaries is extensive (over 400,000 nonpoultry birds have been imported into Japan each year for the last 5 years), the risk of worldwide dissemination of potentially virulent NDVs is considerable. Researchers have speculated that the various types of NDV have been introduced via the importation of various kinds of birds, since NDV can persist in birds in an inapparent carrier state (5,9,10,40).…”
mentioning
confidence: 99%
“…Also, members of the Columbidae family may be infected with APMV-1 adapted to those particular avian species, designated pigeon paramyxovirus 1 (PPMV-1), and are also susceptible to infection by NDV strains that produce clinical disease in chickens (4,16,36,40). Erickson et al (10,11) reported that NDV can be shed from Amazon parrots for more than a year and from budgerigars, conures, mynahs, and black-headed nuns sporadically for up to 83 days.…”
mentioning
confidence: 99%
“…(CA)/ 169302/02] was isolated from a psittacine bird in a northern California pet shop. Several species of psittacine birds can intermittently shed virus in excess of 83 days postexposure (10,11). For this reason, nonclinically infected psittacine birds can potentially transmit NDV, especially since psittacine birds and game fowl are often located on the same premises.…”
mentioning
confidence: 99%
“…Clinical signs may include non specific signs as depression, apathy and ruffled feathers as well as watery greenish diarrhoea, polyuria and later CNS signs. A striking observation was that 5 of 6 species studied, virulent APMV-1 strains were shed for a prolonged period of time (for parrots even more than a year) (Erickson, 1977a). …”
Section: Clinical Signsmentioning
confidence: 96%